Music therapy in children and young people's palliative care - Ludwig, Anna (Music therapist); Schatzberger, Lesley (Jessica Kingsley Publishers, 2019)
" This book brings together music therapists who have worked in the challenging and rewarding world of children's palliative care. Examining techniques from working just with the breath, to technological advances in music therapy such as assistive recording and electronic downloading, it highlights the benefits music therapy can bring when working alongside children and young people. Drawing on the knowledge of expert music therapists, the book provides accessible guidance that practitioners can apply to their own work, including on professional development as part of a multi-disciplinary team, service evaluation, and managing publicity in the hospice setting. It addresses work with different client groups, such as teenagers, and discusses therapy with family members, including siblings. Music therapists and healthcare practitioners will be provided with the tools to reflect on their own professional challenges and deepen their understanding of the important role of music therapy in this sector."